PENERAPAN METODE PEMBELAJARAN IMAJINATIF DALAM MENINGKATKAN PRESTASI BELAJAR MENGARANG BAHASA INDONESIA PADA SISWA KELAS VIII A SMP NEGERI 20 BENGKULU SELATAN TAHUN PELAJARAN 2016/2017 - Risdi Yasik (Universitas Bengkulu, 2018)
In learning activities always found the students who have difficulty in achieving the standard of competence, basic competence, and mastery of learning materials that have been determined. Broadly speaking the difficulty can be a lack of prerequisite knowledge, difficulty understanding learning materials, or difficulty in doing the exercises and solving repetition questions. In particular, the difficulties encountered by learners may include the lack of competence of a particular subject, such as numerical operations in mathematics, or reading and writing in Indonesian language. In order for learners to solve these difficulties need help. Such assistance shall be in the form of remedial or remedial instruction. For the purposes of providing remedial learning should be chosen strategies and steps appropriate after first held a diagnosis of learning difficulties experienced by learners. The purpose of this classroom action research (PTK) is to determine the improvement of student achievement by using Imaginative learning. This study was conducted in 3 cycles. From the results of actions performed proven to improve student achievement by achieving the ideal standard. From 70.58% in cycle 1, it can increase in cycle 2 to 75.33% and cycle 3 reaches 79.88% and has by-passed completion. The results of action research show that Imaginative learning can improve student achievement class VIII A with completeness reach 100% thus Implement Imaginative Learning Effective in Improving Student Achievement of Indonesian Language Lesson in SMP Negeri 20 Bengkulu Selatan..Keywords: Student Learning Achievement, Indonesian Language Lesson in Junior High School, Imaginative Learning